Mitochondrial and Oxidative Stress-Mediated Activation of Protein Kinase D1 and Its Importance in Pancreatic Cancer - Döppler, Heike; Storz, Peter (Frontiers in Oncology, 2017)
Due to alterations in their metabolic activity and decreased mitochondrial efficiency, cancer cells often show increased generation of reactive oxygen species (ROS), but at the same time, to avoid cytotoxic signaling and to facilitate tumorigenic signaling, have mechanism in place that keep ROS in check. This requires signaling molecules that convey increases in oxidative stress to signal to the nucleus to upregulate antioxidant genes. Protein kinase D1 (PKD1), the serine/threonine kinase, is one of these ROS sensors. In this mini-review, we highlight the mechanisms of how PKD1 is activated in response to oxidative stress, so far known downstream effectors, as well as the importance of PKD1-initiated signaling for development and progression of pancreatic cancer.